Rozkład zagregowanych wypłat w ubezpieczeniach komunikacyjnych AC - Migdał, Kinga (The distribution of aggregated claims in automobile AC insurance portfolio, 2006)
The main idea of insurance is that an insurance company assumes responsibility to compensate for financial losses resulting from any damage insured against in insurance contract, in return for a premium paid by the customer. That’s why the basic element of insurance activity is proper premium calculation. The model of insurance portfolio in this article is the set of policies generating claims in random moments of lime. The basis of appropriate insurer’s premium calculation is statistical methods application. This helps to analyse events in order to determine the frequency at which these events occur as well as the amount of financial losses involved. In this paper the real data from the portfolio of automobile autocasco (AC) insurance policies are taken into consideration. The purpose of this paper is to settle the statistical model of aggregated claims amount generated from the portfolio in the one year time period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 89-98